Analysis of Factors Affecting The Management of Overall Energy Efficiency of Tractor-Implement by Real-Time Performance Monitoring - N Kazemi; M Almassi; H Bahrami; M.J Shaykhdavoodi; M Mesgarbashi (Journal of Agricultural Machinery, 2014)
Overall energy efficiency (OEE) is an important indicator of energy consumption in tillage operations. Tillage energy was studied objectivity to accurately measure the OEE of MF399-4WD tractor. The tractor was equipped with different types of sensors to measure and calibrate the required data including: fuel consumption, actual forward speed, wheel speed and slippage, engine speed, draft and drawbar power. The data were recorded with frequency of 1000 Hz and transmitted by employing a suitable wireless technology in the range of up to1.5 km to the user's personal computer and is stored in Excel format. The hardware and the software program, which was written in C# language, simultaneously monitor the changes in functional parameters and the monitoring can be done even from far away and via the Internet. The split factorial experiment with three factors including ballast, selected gear ratio and two wheel drive configurations (two and four wheel drive) was employed to perform analysis of variance (ANOVA), POST ANOVA AND PATH ANALYSIS. The results show that the performance of remote monitoring devices installation was very accurate and high-quality. Furthermore, statistical analysis showed that three parameters including slippage, fuel consumption and tractor Power Equivalent (PEQ) were the most effective parameters on overall energy efficiency of tractors – tillage. The variance analysis showed that the effect of gear ratio and drive configuration on the OEE were also significant at the one percent level. However, ballasting had no significant effect on the OEE.